(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
This study discusses strategies for resolving bad debts guaranteed by mortgage rights at PT. Kerinci Development People’s Credit Bank. One method is to make efforts to save credit through a repayment plan (rescheduling) based on Bank Indonesia Circular Letter No.26/4/BPPP dated 29 May 1993. The bank also provides verbal and written warnings to debtors before taking further action. In addition, credit settlement is carried out using a family approach (non-litigation) through a mutual agreement to sell collateral, in accordance with applicable legal provisions